RNA Editing and Short Variant of Serotonin 2C Receptor mRNA in Neuronally Differentiated NG108-15 Cells - Michihisa Tohda; Monrudee Sukma; Hiroshi Watanabe (Elsevier, 2004)
Two types of serotonin 2C subtype receptor mRNA, receptor-type and short variant, has been reported. The expression of the receptor-type mRNA could be detected as well as the short variant in NG108-15 cells by using a high temperature stable reversetranscriptase and the expression of the receptor-type mRNA was enhanced in drug-induced neuronal differentiated cells. The deleted sequence of the short variant include the RNA editing site by adenosine deaminase. Analysis of the sequence at the editing site revealed that the mRNA of undifferentiated cells was highly edited at sites A and B and that cytosine deaminase activity may also be involved in neuronal differentiation. Keywords:: serotonin, RNA editing, short variant, deaminase, neuronal differentiation